Annual Report to the Nation on the Status of Cancer, part II: Recent changes in prostate cancer trends and disease characteristics - Negoita, Serban; Feuer, Eric J.; Mariotto, Angela; Cronin, Kathleen A.; Petkov, Valentina I.; Hussey, Sarah K.; Benard, Vicki; Henley, S. Jane; Anderson, Robert N.; Fedewa, Stacey; Sherman, Recinda L.; Kohler, Betsy A.; et al. (Cancer, 2018)
BACKGROUND Temporal trends in prostate cancer incidence and death rates have been attributed to changing patterns of screening and improved treatment (mortality only), among other factors. This study evaluated contemporary national‐level trends and their relations with prostate‐specific antigen (PSA) testing prevalence and explored trends in incidence according to disease characteristics with stage‐specific, delay‐adjusted rates. METHODS Joinpoint regression was used to examine changes in delay‐adjusted prostate cancer incidence rates from population‐based US cancer registries from 2000 to 2014 by age categories, race, and disease characteristics, including stage, PSA, Gleason score, and clinical extension. In addition, the analysis included trends for prostate cancer mortality between 1975 and 2015 by race and the estimation of PSA testing prevalence between 1987 and 2005. The annual percent change was calculated for periods defined by significant trend change points. RESULTS For all age groups, overall prostate cancer incidence rates declined approximately 6.5% per year from 2007. However, the incidence of distant‐stage disease increased from 2010 to 2014. The incidence of disease according to higher PSA levels or Gleason scores at diagnosis did not increase. After years of significant decline (from 1993 to 2013), the overall prostate cancer mortality trend stabilized from 2013 to 2015. CONCLUSIONS After a decline in PSA test usage, there has been an increased burden of late‐stage disease, and the decline in prostate cancer mortality has leveled off. Cancer 2018;124:2801‐2814. © 2018 American Cancer Society For the first time, the US cancer surveillance community has performed an analysis of long‐term trends in the incidence of prostate cancer by stage with delay‐adjusted rates. According to nationwide cancer registry and vital registration data, prostate cancer incidence rates for distant‐stage disease have increased and mortality rates for all stages combined have leveled off in the United States since the US Preventive Services Task Force recommendations against prostate‐specific antigen–based screening.See also pages 2785‐800 and 2690‐2.